Antibicrobial and cytotoxic compounds of Scorodocarpus borneensis (Olacaceae) and Glycosmis calcicola (Rutaceae) - Wiart, Christophe (2001)
The extracts of plants collected from the forest of Northern Malay Peninsula were tested against bacteria, fungi and CEM-SS leukemia cel1 line. Gram-positive Bacillus cereus and Gram-negative Pseudomonas aeruginosa which are commonly involved in skin infections, have been used for screening antibacterial activity whereas Candida lipolytica, Saccharomyces cerevisae, Saccharomyces lipolytica, and Aspergillus ochraceous have been used for screening antifungal activity. The crude extract from the seeds of Scorodocarpus bomeensis showed a strong cytotoxic activity against CEM-SS leukemia cell-line and antimicrobial activities. A bioassay-guided separation had been carried out to separate the active constituents of the seeds. This resulted in the isolation and identification of an aliphatic sulfur compound, bis-(methylthiomethyl)disulfide, and a new indole alkalOld, 13-docosenoyl serotonme from the petroleum ether extract A new sesquiterpene, scopotin, has been isolated from the chloroform extract of the seeds Another sesquiterpene, cadalene-p-carboxyhc acid, has been isolated from the bark of this species bis-(Methyithiomethyl)-disulfide appeared as the most active compound and the major constttuent of the seeds extract of Scorodocarpus borneensis it acted significantly on a methicillin resistant strain of Staphylococcus aureus and showed a strong Cytotoxic activity against CEM-SS leukemia and KU812F chronic myelogenous leukemia cell lines 13-Docosenoyl serotonme showed a moderate Cytotoxic activity against CEM-SS leukemia cell line Scopotin showed a moderate antimicrobial activity and a strong Cytotixic effect against CEM-SS leukemia cell line The crude petroleum ether extract and bis-(methyithtomethyl)disulfide strongly inhibited the growth of pathogen fungi and was formulated m external preparation by usmg commercial paraffin as exipient. This preparation exhibited drastic antifungal activities in vitro and in VIVO The acute toxicity of the crude petroleum ether extract was found to be inferior to phenobarbital in mice with LD50 at 275 mg/kg The skin irritancy test was performed on rabbits and it showed that this preparatlOn had an irritancy level acceptable by the FDA. Antimicrobial and cytotoxic activities were also performed on methylgerambullin and desmethoxyzanthophylline which were previously isolated from Glycosmis calcicola (Rutaceae). Methylgerambullin showed a strong cytotoxic activity against CEM-SS leukemia, melanoma HACCl, and colon cancer HT29 cell lines whereas desmethoxyzanthophylline has moderate activity against Bacillus cereus, Pseudomonas aeruginosa and CEM-SS leukemia cell line.